2014
DOI: 10.1007/s10933-014-9800-8
|View full text |Cite
|
Sign up to set email alerts
|

Modern influences on chironomid distribution in western Ireland: potential for palaeoenvironmental reconstruction

Abstract: Ireland provides a unique setting for the study of past climates, as its climate is dominated by westerly airflow from the North Atlantic and readily responsive to changes in North Atlantic circulation patterns. Although there has been substantial research on Ireland's past environments, quantitative palaeolimnological research, especially chironomid-based research, has been lacking. In order to further develop chironomid-based palaeolimnological investigations, a calibration set was constructed to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 56 publications
(64 reference statements)
5
18
0
Order By: Relevance
“…The training set has a MJT gradient of 16.6 • C and the RMSEP represents 13.8 % of the scalar length of the MJT gradient. This is comparable with most chironomid-based transfer function models including those developed from northern Sweden with 100 lakes (r 2 = 0.65, Larocque et al, 2001), western Ireland with 50 lakes (r 2 = 0.60, Potito et al, 2014) and Finland with 77 lakes (r 2 = 0.78, Luoto, 2009) representing 14.7, 15 and 12.5 % of the scalar length of the temperature gradient, respectively, but less robust than the combined 274-lake transfer function developed from Europe (r 2 = 0.84, RMSEP representing 10.4 % of the scalar length of the MJT gradient) (Heiri et al, 2011). Despite of the relatively lower model coefficient (r boot = 0.63), we observe that by having a large number of lakes in the calibration set, the distribution of the sites along the MJT gradient is relatively even (Fig.…”
Section: Reliability Of the Environmental And Chironomid Datasupporting
confidence: 81%
“…The training set has a MJT gradient of 16.6 • C and the RMSEP represents 13.8 % of the scalar length of the MJT gradient. This is comparable with most chironomid-based transfer function models including those developed from northern Sweden with 100 lakes (r 2 = 0.65, Larocque et al, 2001), western Ireland with 50 lakes (r 2 = 0.60, Potito et al, 2014) and Finland with 77 lakes (r 2 = 0.78, Luoto, 2009) representing 14.7, 15 and 12.5 % of the scalar length of the temperature gradient, respectively, but less robust than the combined 274-lake transfer function developed from Europe (r 2 = 0.84, RMSEP representing 10.4 % of the scalar length of the MJT gradient) (Heiri et al, 2011). Despite of the relatively lower model coefficient (r boot = 0.63), we observe that by having a large number of lakes in the calibration set, the distribution of the sites along the MJT gradient is relatively even (Fig.…”
Section: Reliability Of the Environmental And Chironomid Datasupporting
confidence: 81%
“…of the scalar length and this is comparable with most other transfer functions (e.g. Potito et al, 2014). It has been observed that data sets with large temperature gradients naturally have larger errors but this in no way diminishes the value of the reconstruction.…”
Section: The Transfer Functionsupporting
confidence: 73%
“…For the last 6000 years, human settlement and active farming has been a prominent feature on the Irish landscape and, as a result, lakes on the island are rarely isolated from such impacts. In order to confidently reconstruct Irish temperatures through the Holocene, it must first be determined if Irish-based temperature inference models (Potito et al, 2014) can adequately reconstruct temperature at sites with low to moderate human influences.…”
Section: Introductionmentioning
confidence: 99%
“…Even removed from prehistoric settlement, reconstructions of relatively modest Holocene temperature change in this maritime region would prove difficult using extra-regional training sets with large temperature ranges and relatively large associated error ranges. A recent chironomid-based inference model developed from 50 lakes in western Ireland (r 2 jack = 0.60, RMSEP = 0.57°C, maximum bias = 0.63°C) may help to overcome these past difficulties in Holocene temperature reconstruction (Potito et al, 2014). The relatively small temperature range in the training set, and the accompanying small RMSEP, lends the inference model greater applicability for reconstructing Ireland's subdued Holocene temperature fluctuations (Potito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation